PREDIKSI LAJU EROSI MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) DI DAERAH WADUK BENANGA LEMPAKE KOTA SAMARINDA, KALIMANTAN TIMUR - yunianto Setiawan; Tri Setyaningrum; Waryati Waryati (Jurnal Teknologi Lingkungan UNMUL, 2017)
AbstractSoil erosion is one form of soil degradation or transported to another place by a natural medium. One of the effects of erosion are silting in water bodies such as reservoirs or lakes. The purpose of this study was to determine the rate of erosion and its factors that cause erosion in the reservoir area of Benanga Lempake Samarinda. The amount of erosion that occurs can be determined using the equation Universal Soil Loss Equation (USLE) by Wischmeier and Smith (1978), which consists of factors erosivitas rainfall, soil erodibility, length and slope, crop management and soil conservation. The results of the processing overlapping of the four map erosion factors by using software Geographic Information System (GIS) resulting in erosion value and distribution class erosion. The Results of analysis data obtained value erosion in the reservoir area Benanga Lempake Samarinda are 6.496,62 ton/ha/year. Based on the analysis and prediction of erosion of the magnitude of the erosion can lead to sedimentation occurred in Benanga Lempake Samarinda Reservoir, so that the incoming water due to rain and water runoff from the Karang Mumus Watershed is not dammed by the dam so that the water overflowed and caused flooding. Erosion prevention efforts need to be done such as soil and water conservation. Keywords : Soil Erosion , Reservoir, Geographic Information Systems.